Multiple metals exposure and estimated pulse wave velocity: a cross-sectional analysis of the US adults - Zhou, Shijie; Xiao, Zhihao; Shi, Boyu; Fu, Zuqiang; Wang, Shourui; Li, Wenxiang; Liu, Zhiwei; Liu, Qian; Gu, Xinxin; Gu, Aihua (Frontiers in Public Health, 2025)
Background and objectivesArterial stiffness has been demonstrated to be associated with a range of adverse cardiovascular events. Nevertheless, the epidemiological evidence on the association between metal exposure and arterial stiffness remains inconclusive.MethodsThe data concerning 12 urine metals were derived from the National Health and Nutrition Examination Survey (NHANES) conducted from 2003 to 2016. Multiple linear regression and restricted cubic spline (RCS) analyses were applied to explore the potential linear and nonlinear associations between urine metal and ePWV. A parallel mediation analysis was conducted in order to explore the potential intermediate factors in metal-induced ePWV elevation. Weighted quantile sum (WQS) regression and Quantile g-computation (Qgcomp) were conducted to estimate the individual and combined associations between urine metal and ePWV.ResultsFollowing adjustment for the relevant covariates, it was found that urine Cd, Pb, Co, and U were found to be significantly correlated to elevated ePWV in both the multiple linear regression and the RCS model. Mediation analysis revealed that high - density lipoprotein (HDL) and total cholesterol (TC) might be partly implicated in the correlation between urine metal and ePWV. WQS regression and Qgcomp analyses consistently indicate a positive correlation between exposure to mixed metals and elevated ePWV, with Cd and Pb identified as the primary contributors to this phenomenon.ConclusionThe present study indicated a significant association between the presence of a mixture of metals and elevated ePWV, with Cd and Pb identified as the primary risk factors. And HDL and TC might participate in mediating mixed metals exposure induced ePWV changes.